Poverty through a gender lens: Evidence and policy review on gender and poverty - Bennett, F; Daly, M (Department of Social Policy and Intervention, 2014)
This review forms part of the Joseph Rowntree Foundation’s programme to develop a set of evidence-based anti-poverty strategies for the UK. The remit was to identify and analyse evidence on the links between gender and poverty, and possible reasons for them; and to examine the impact on these links of specific policies and overall policy approaches. On the basis of the findings, the review was to make recommendations for gender-oriented measures to prevent and tackle poverty linked to gender and highlight any gaps in the evidence base. The review did not cover sexual orientation or family structure, as these were the subjects of separate reviews. Based on a rigorous and reflective review of the evidence, this report maximises the knowledge available from existing studies and evaluations. But it also argues that very few of these have focused in practice on the links between gender and poverty; and that analytical methods need to be further developed, in order to disentangle these links more fully and investigate the gender impact of policies affecting poverty or the risk of poverty.